Influences of methane and propane on the explosion characteristics of polymethyl methacrylate and acrylonitrile butadiene styrene dusts. Issue 2 (16th October 2021) - Cheng, Jianwei; Qi, Chang; Zhang, Jing; Zhao, Peitao; Qin, Yi; Wang, Yue; Zhao, Gang; Gao, Ke
Abstract: Polymethyl methacrylate (PMMA) and acrylonitrile butadiene styrene copolymers (ABS) are widely applied to industrial production, with the risk of explosion mixed with combustible gas increasing gradually. A 20 L spherical explosive device was used to study the variation pattern of the explosion characteristics of four gas–dust mixtures: methane/PMMA, methane/ABS, propane/PMMA, and propane/ABS mixtures. The results showed that despite adding methane and propane, PMMA and ABS dusts within the range of minimum explosion concentration are still likely to explode. The comparative analysis shows that propane is more chemically reactive than methane and PMMA and ABS dusts mixed with propane are more dangerous than those mixed with methane. Meanwhile, it was found that as the concentration of methane and propane increases, the maximum explosion pressure P max, maximum explosion pressure rise rate (d P /d t )max, and explosive index K of the dusts rise as well, but the increasing trend remains steady. The single‐phase methane and propane have higher maximum explosion pressure and explosive index than the gas–dust mixture, with the lowest maximum explosion pressure and explosive index found in the single‐phase PMMA and ABS dusts. With methane and propane mixed, the explosion hazard of PMMA and ABS dusts is intensified from St1 to St3. This study reveals the explosion characteristics of PMMA and ABS dusts, providing a basis for ensuring a safe working environment, preventing and controlling explosion accidents, and reducing the destructiveness of accidents.